Propagation Properties and Application of Radially Polarized Partially Coherent Twisted Vortex Hermite‐Gaussian Schell‐Model Beams. Issue 6 (6th May 2022) - Pan, Keming; Xu, Jia; Zeng, Zishuai; Zhao, Daomu
Abstract: A class of radially polarized partially coherent twisted vortex Hermite‐Gaussian Schell‐model (RPPCTVHGSM) beams is introduced. The analytical propagation formula for the cross‐spectral density matrix of this beam family is derived. It is found the component of the spectral density and the degree of polarization show twist effects upon propagation. Then, such focused beam family's feasibility to accomplish stable 3D optical capture on both low‐ and high‐index particles is theoretically and numerically analyzed. The results show that utilizing the nonzero order RPPCTVHGSM beam has no limit on the refractive index of particles. Compared with the center of the geometric focal plane, real equilibrium points will shift. Finally, the exact offset of the genuine capture point in each direction is obtained by taking the second‐order RPPCTVHGSM beam as an example. The applications of the work are envisioned in material surface processing and tracking mobile military. Abstract : A class of radially polarized partially coherent twisted vortex Hermite‐Gaussian Schell‐model beams is introduced. It is found that the spectral density and the degree of polarization show twist effects upon propagation. Such focused beam family's feasibility to accomplish stable 3D optical capture on both low‐ and high‐index particles is analyzed, and it is found that the real equilibrium points will shift.